“MERTELU” PROFIT-SHARING AGREEMENT AS THE ATTEMPT TO INCREASE THE INCOME OF TUBEROSE TENANT FARMERS - Nasikh - Nasikh (Universitas Padjadjaran, 2021)
Farmer communities in Pasuruan regency, East Java, still rely on the agriculture sector to generate their income. Tuberose farmers, in particular, find difficulty in dealing with land ownership. They, who are skilful and expert, are lack of capital ownership, especially the land. The majority of tuberose farmers depend on “mertelu” profit-sharing as their daily income alternative. This study aims to analyse “mertelu” profit-sharing as an attempt to increase the tuberose farmers’ incomes in Pasuruan regency, East Java. The research is done by a purposive sampling in Bangil, Rembang sub-districts, Pasuruan regency. This study uses a qualitative descriptive approach with the instrument of microeconomic theory. Data are collected by interviews with land owners and the tuberose farmers. The research finding shows that “mertelu” profit-sharing becomes one of the alternatives to increase the tuberose farmers’ income. Nevertheless, the tuberose farmers in Pasuruan regency, East Java, feel that “mertelu” profit-sharing has not been able to improve their income significantly.